TRANSP modelling of total and local neutron emission on MAST. (14th January 2015) - Klimek, I.; Cecconello, M.; Gorelenkova, M.; Keeling, D.; Meakins, A.; Jones, O.; Akers, R.; Lupelli, I.; Turnyanskiy, M.; Ericsson, G.
Abstract: The results of TRANSP simulations of neutron count rate profiles measured by a collimated neutron flux monitor–neutron camera (NC)—for different plasma scenarios on MAST are reported. In addition, the effect of various plasma parameters on neutron emission is studied by means of TRANSP simulation. The fast ion redistribution and losses due to fishbone modes, which belong to a wider category of energetic particle modes, are observed by the NC and modelled in TRANSP.